POEM AS A POLITICAL ACT; SCANNEL’S WORLDVIEW ON WALKING WOUNDED - Ida Rosida; Sulhizah Wulan Sari (Wanastra: Jurnal Bahasa dan Sastra, 2017)
This study is aimed at revealing worldview of the poet toward war that is reflected in Walking Wounded by Vernon Scannel. The methode used in the research is descriptive qualitative supported by Genetic structuralism theory by Lucien Goldman that focus on analyzing internal and external structures of a literary work. Through a deep investigation of the internal structure of the poem, biographical interpretation of the poet, and socio-historical background in the creation of the poems, it is finally revealed the worldview of the poet toward the war. Result shows that war is not only devastated physical buildings but humanity. War is absolutely giving nothing but misery and humiliation for humanity.This study is important in adding up knowledge especially on how a poem is investigated through its internal and external structure. Moreover, the most significant thing of this study reveals that poem could be a political activism of the poet. Revelation of the worldview of the poet toward the war enlarges the opportunity to change the worldview of every human in the world especially on how important the humanity is and how important is it to keep the world peace.